Intestinal pseudo-obstruction in patients with amyloidosis: clinicopathologic differences between chemical types of amyloid protein. Issue 10 (October 1993) - Tada, S; Iida, M; Yao, T; Kitamoto, T; Yao, T; Fujishima, M
Abstract : A clinicopathologic study was made of 16 patients with amyloidosis and with clinical signs of intestinal pseudo-obstruction. amyloid deposits in the small intestine were proved in all cases by endoscopic or intra-operative biopsies, and immunohistochemical study identified the chemical types of amyloid protein: amyloid A protein (AA) in 13 cases, light chain protein (AL) in two, and beta 2-microglobulin (AH) in one. Clinically, an acute self limiting obstructive condition was evident in 13 cases with AA, and 12 of them returned to normal bowel function after receiving total parenteral nutrition. Two cases with AL and one with AH presented chronic, intermittent, obstructive symptoms, and medical treatment, including total parenteral nutrition, was ineffective with no recovery of intestinal propulsion. Pathological examination of the necropsy specimens in seven cases showed considerable differences in the preferential sites of gastrointestinal deposits between the chemical types of amyloid; extensive infiltration and replacement of the muscularis propria by amyloid deposits throughout the gastrointestinal tract, especially the small intestine, were found in the AL and the AH cases, while amyloid deposits in the myenteric plexus without appreciable muscle infiltration were shown in the AA cases. These results show that intestinal pseudo-obstruction in patients with amyloidosis is caused by either myopathy or neuropathy, and that chemical types of amyloid may determine which of the two factors has the dominant affect on the bowel function.